Ձիու թեմատիկան Բաքիի դիվանում - Լուսինե Խաչատրյան; Անի Սարգսյան (ՀՀ ԳԱԱ հրատ.)
The horses have always had an important tole in the Turkic peoples’ lifestyle. Let alone their economic advances, they are even reflected in folklore and literature. The representatives of Ottoman Divan Literature wrote гаіщіууе devoted to different kind of horses. The paper is mainly focused on the horse-names that can be found in Baki’s Divan. The etymologies of various horse-names are also represented in the article.
Keywords: Language and Literature